Housing, husbandry and handling of rodents for behavioral experiments. - Deacon, R (2006)
Most animals used in research are rodents, mainly mice because of their predominance in genetics and molecular biology. This article attempts to provide an introduction to mice and rats: health considerations (of the experimenter); choice of species, age, strain and sex; housing and environmental enrichment; and animal identification, handling and dosing. These considerations apply to animal work in general; the rest of the article focuses on the preliminary aspects of behavioral testing, including a protocol for an open field test. This procedure is traditionally associated with activity measurements, and although automated versions are readily available these days, the latter are expensive and may be unavailable in many non-behavioral departments. Moreover, particularly when testing novel genetically modified animals or pharmacological agents, there is no substitute for direct visual observation to detect abnormal signs in the animals: for example, ptosis, piloerection, tremor, ataxia or exophthalmos. The open field test can be adapted in several ways: to assess general behavior and activity (similar to a primary screen in the pharmaceutical industry) or to measure memory (habituation) or anxiety.